Integrin β1 Optimizes Diabetogenic T Cell Migration and Function in the Pancreas - Espinosa-Carrasco, Gabriel; Le Saout, Cécile; Fontanaud, Pierre; Michau, Aurélien; Mollard, Patrice; Hernandez, Javier; Schaeffer, Marie (Frontiers in Immunology, 2018)
T cell search behavior is dictated by their need to encounter their specific antigen to eliminate target cells. However, mechanisms controlling effector T cell motility are highly tissue-dependent. Specifically, how diabetogenic T cells encounter their target beta cells in dispersed islets throughout the pancreas (PA) during autoimmune diabetes remains unclear. Using intra-vital 2-photon microscopy in a mouse model of diabetes, we found that CXCR3 chemokine downregulated CD8+ T cell motility specifically within islets, promoting effector cell confinement to their target sites. By contrast, T cell velocity and directionality in the exocrine tissue were enhanced along blood vessels and extracellular matrix fibers. This guided migration implicated integrin-dependent interactions, since integrin blockade impaired exocrine T cell motility. In addition, integrin β1 blockade decreased CD4+ T cell effector phenotype specifically in the PA. Thus, we unveil an important role for integrins in the PA during autoimmune diabetes that may have important implications for the design of new therapies.